Oil-based drilling fluid plugging agent and preparation method thereof

CN119351066AActive Publication Date: 2025-01-24SINOPEC OILFIELD SERVICE CORPORATION +2
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411474504.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-01-24
Estimated Expiration
2044-10-22

AI Technical Summary

Technical Problem

一方面,封堵剂为粉剂,对于地层微裂隙而言,由于难以实现均匀分布,存在大颗粒堵塞裂缝、小颗粒随钻井液漏走的情况,即“进不去、留不住”的问题

Benefits of technology

[0033] 4) After the conventional powder or water-based compound sealing materials enter the fracture with the drilling fluid, the nano- and micron-sized small particle sealing materials enter and lose quickly, while the millimeter-sized large particles cannot enter and form inside the fracture. Bridging and step-by-step filling result in poor sealing effect. The present invention uses asphalt particles as carriers to make 0.5-3mm granular leakage plugging materials, which are divided into nanometer, micron and millimeter grades according to the different characteristics of the raw materials. The "leak plugging capsule" mechanism is used for comprehensive plugging. By plugging the leakage The capsule migrates to cracks or cracks, asphalt Under the action of formation high temperature and wellbore pressure, rigid and elastic plugging materials of different particle sizes are released at the same time, and quickly aggregate to form a bridge. Subsequently, nano-scale and micron-scale materials are gradually filled, greatly improving the stability and sealing of the plugging layer. effect, effectively improving the bridging speed and success rate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005095683330000061
    Figure BDA0005095683330000061
  • Figure BDA0005095683330000071
    Figure BDA0005095683330000071
  • Figure BDA0005095683330000081
    Figure BDA0005095683330000081
Patent Text Reader

Abstract

The invention relates to an oil-based drilling fluid plugging agent and a preparation method thereof. The oil-based drilling fluid plugging agent comprises granular materials prepared from the following components in percentage by mass: 15-28 wt% of asphalt powder; 6 to 16 wt% of organic clay; 25 to 40 wt% of rock fiber; 5 to 12 wt% of nanometer S < iO2 >; 8 to 15 weight percent of sepiolite; 8 to 18 wt% of elastic graphite; and 10 to 20 weight percent of polyurethane (TPU) powder particles. The oil-based drilling fluid has the advantages of good compatibility, high efficiency and good plugging effect, can repair well wall stratum defects, prevent borehole leakage, enhance the residence and plugging effect of the oil-based drilling fluid in stratum microfractures, improve the well wall stability, and effectively play roles in plugging and strengthening the well wall.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of wellbore plugging in oil well operations, and in particular to an oil-based drilling fluid plugging agent and a preparation method thereof. Background Art

[0002] Oil-based drilling fluid has strong inhibitory effects on shale and excellent lubricity, so it is widely used in the construction of horizontal sections of shale wells. However, the horizontal sections of shale have developed bedding and microcracks, which are prone to well leakage and well wall collapse. The loss of oil-based drilling fluid leads to increased production costs and a long post-well collapse processing time, which seriously affects the exploration and development of shale oil and gas wells.

[0003] The plugging agent used for plugging wellbore in oil well operation is usually in liquid or powder form. For example, publication number CN116948609A discloses the preparation of a nano plugging agent and an oil-based drilling fluid, which is formed by the reaction of emulsified asphalt, fine fibers, ammonium acrylate and modified nano-silicon dioxide. Micro-nano liquid plugging agents are used to plug micro-fracture formations, but after being added to oil field drilling fluids, due to unreasonable material particle size structure, lack of elastic plugging materials and other reasons, there is a problem of poor compatibility with oil-based drilling fluids and inability to effectively plug and stabilize the well wall.

[0004] For another example, CN118389130A discloses a shale oil-based drilling fluid filtration reduction plugging agent and a preparation method thereof, wherein the shale oil-based drilling fluid filtration reduction plugging agent comprises the following components by weight: 15-25 parts of asphalt powder, 10-20 parts of modified rubber powder, 10-20 parts of organic lignite, 5-10 parts of emulsifier, 10-20 parts of oil-absorbing resin, 10-20 parts of sepiolite, 10-15 parts of polyamide wax, 10-20 parts of solvent oil, and 10-30 parts of water. The shale oil-based drilling fluid filtration reduction plugging agent has good filtration reduction and shale plugging effects, and quickly forms a tight sealing layer in sandstone, shale and micro-crack channels through skeleton plugging, flexible filling and expansion elastic release. On the one hand, the plugging agent is a powder. For micro-cracks in the formation, it is difficult to achieve uniform distribution, and there is a situation where large particles block the cracks and small particles leak away with the drilling fluid, that is, the problem of "cannot enter and cannot be retained". On the other hand, the modified rubber powder and sepiolite in the components are used as the skeleton, which is easy to deform when heated and compressed, and the plugging effect needs to be further improved. Summary of the invention

[0005] The purpose of the present invention is to solve the above-mentioned technical problems and to provide an oil-based drilling fluid plugging agent with good compatibility, high efficiency, good plugging effect, which can repair well wall formation defects, prevent wellbore leakage, enhance the residence and plugging effect of oil-based drilling fluid in formation microcracks, improve well wall stability, and effectively play the role of plugging and strengthening the well wall.

[0006] The present invention also provides a method for preparing the environmentally friendly lubricant for drilling fluid with extremely simple process and low cost.

[0007] The oil-based drilling fluid plugging agent of the present invention is characterized by comprising a granular material made of the following components in percentage by mass:

[0008] Asphalt powder: 15-28wt%;

[0009] Organoclay: 6-16wt%;

[0010] Rock fiber: 25-40wt%;

[0011] Nano-SiO2: 5-12wt%;

[0012] Sepiolite: 8-15wt%;

[0013] Elastic graphite: 8-18wt%;

[0014] Polyurethane (TPU) powder particles: 10-20wt%.

[0015] The particle size of the granular material is 0.5 to 3 mm.

[0016] The rock fiber has a diameter of 500-800 nm and a length of 100-200 μm.

[0017] The particle size of the nano SiO2 is 300-800nm;

[0018] The sepiolite is sepiolite fiber with a diameter of 15 to 30 μm and a length of 1 to 2 mm.

[0019] The elastic graphite particles have a particle size of 5 to 40 μm.

[0020] The particle size of the polyurethane (TPU) powder particles is 300-500 μm.

[0021] The rock fiber is made of basalt and granite as raw materials, and is produced through crushing, high-temperature melting, alloy drawing and cutting.

[0022] The preparation method of the rock fiber is as follows: basalt and granite are mixed and crushed into fine particles of 40 to 80 meshes in a mechanical crusher at a mass ratio of 7:3, and then put into a basalt furnace, melted and mixed evenly at a temperature of 1600°C, and then drawn at high speed through an alloy wire drawing plate to form fibers, and the surface of the drawn fibers is infiltrated with polyether modified silicone SF309, and then dried and processed by a cutting machine to obtain the fiber.

[0023] The method for preparing the oil-based drilling fluid plugging agent is characterized by comprising the following steps:

[0024] S1, put asphalt powder into the reactor, keep the stirring speed of the reactor at 100r / min, then heat the reactor to 120°C, add organoclay, sepiolite and polyurethane (TPU) in sequence, and stir for 1 hour;

[0025] S2, add rock fiber, elastic graphite and nano-SiO2 to S1 in sequence and stir for 3 hours;

[0026] S3, extrude S2 into granules through a twin-screw extruder, and then crush and sieve to make a granular material.

[0027] The particle size of the granular material is 0.5 to 3 mm;

[0028] In view of the problems existing in the background technology, the inventor has made the following improvements:

[0029] 1) Specially add rock fiber. The raw material of rock fiber is mineral rock. On the one hand, its physical properties are highly compatible with the formation. As a rigid bridging material, these particles can stably bridge the pore throats and narrow cracks of the leakage channel, are not easily deformed by heat and pressure, and are helpful to form a plugging layer skeleton; on the other hand, due to its nanometer diameter (diameter is 500-800nm) and micrometer length, it is particularly suitable for micrometer-level pores and cracks; and, the rock fiber has a low degree of agglomeration and can be stably, uniformly and stably dispersed in an oil phase environment. It has good compatibility with oil-based drilling fluids and forms a firm fit with formation cracks. Compared with other fiber materials, it has a better plugging effect on micropores and microcracks. Here, considering that the length of the rigid material particles has a direct impact on the bridging effect, the preferred length of the rock fiber should be 100-200μm. Rock fibers of this length can better build a bridging network in the crack position to achieve the purpose of step-by-step filling and plugging in the crack. If the length is too long, it will bridge at the crack gate position, and if it is too short, it will not be able to form a grid structure.

[0030] Furthermore, the inventors preferred to use basalt and granite as the raw materials of rock fiber. Considering that basalt has the characteristics of compression and bending resistance, heat absorption and heat storage, and wear resistance, and granite can improve wear resistance and corrosion resistance, the two are compounded to prepare rock fiber with good toughness and strength, which significantly improves the pressure bearing effect of the formation, and can meet the requirements of high temperature, high pressure, and strong alkaline environment underground. Among them, considering the requirements of wire drawing process and physical strength characteristics of rock fiber, the mass ratio of basalt and granite is 7:3. Too high a dosage of basalt will reduce the fiber strength, and too low a dosage will increase the difficulty of the fiber preparation process. In the preparation step, the surface of the drawn fiber is infiltrated with polyether-modified silicone SF309, which can also improve the dispersion ability of the fiber in the drilling fluid and further improve the compatibility performance.

[0031] 2) Using elastic graphite and polyurethane (TPU) powder as elastic filling materials, on the one hand, using materials with different particle sizes (the elastic graphite particle size is 5-40 μm, the polyurethane (TPU) powder particle size is 300-500 μm) to achieve graded filling, on the other hand, elastic graphite has its unique flexibility and resilience, polyurethane (TPU) powder has good hardness, the two compound can complement each other, taking into account the needs of elasticity and hardness, can enter the gap under a certain degree of external force, and then restore its original shape, and have good hardness and low rigidity, can withstand large deformation without breaking, and then can be filled according to the form of cracks and pores in the leakage formation. At the same time, in addition to the role of carrier, asphalt also has good elastic deformation, good retention in the oil phase environment, and repairs the well wall. The addition amount is preferably 15-28wt%, too much will lead to uneven distribution of plugging materials, too little will not play the role of carrier, reducing the plugging effect.

[0032] 3) Adding sepiolite fiber utilizes its excellent adsorption and sealing properties to effectively improve the pressure bearing capacity of the formation after plugging. The diameter of the sepiolite fiber is further controlled to be 15-30 μm and the length is 1-2 mm. The sepiolite fiber of this size has good fluidity and sealing performance. The added amount is controlled to be 8-15wt%. Too much will affect the rheological properties of the drilling fluid, and too little will reduce the sealing effect on the cracks. Adding organic clay can improve the compatibility with the oil-based drilling fluid.

[0033] 4) After the conventional powder or aqueous compound plugging material enters the crack with the drilling fluid, the nanometer-level and micrometer-level small-particle plugging material enters and drains quickly, while the millimeter-level large particles cannot enter, and cannot form bridges and fill step by step inside the crack, resulting in poor plugging effect. The present invention uses asphalt particles as carriers to make 0.5-3mm granular plugging materials, which are graded in nanometers, micrometers and millimeters according to the different characteristics of the raw materials, and adopts the "plugging capsule" mechanism for comprehensive plugging. By transporting the plugging capsule to the crack mouth or crack gate, the asphalt is subjected to the high temperature of the formation and the wellbore pressure, and releases rigid and elastic plugging materials of different particle sizes at the same time, and quickly gathers to form bridges. Subsequent nanometer-level and micrometer-level materials are gradually filled, which greatly improves the stability and plugging effect of the plugging layer, and effectively improves the bridging rate and success rate.

[0034] The plugging agent of the invention has good compatibility, high plugging efficiency and good effect, can repair well wall formation defects, prevent wellbore leakage, enhance the residence and plugging effect of oil-based drilling fluid in formation microcracks, improve well wall stability, and effectively play the role of plugging and strengthening the well wall. DETAILED DESCRIPTION

[0035] Preparation example of rock fiber:

[0036] Basalt and granite are mixed and crushed into 40-80 mesh fine particles in a mechanical crusher at a mass ratio of 7:3, and then put into a basalt furnace. After being melted and mixed evenly at a temperature of 1600°C, they are drawn at high speed through an alloy wire drawing plate to form fibers. The surface of the drawn fibers is infiltrated with polyether modified silicone SF309 for 10 minutes, dried at 200°C for 30 minutes, and then processed by a cutting machine to obtain rock fibers with a diameter of 500-800nm ​​and a length of 100-200μm.

[0037] Ingredients:

[0038]

[0039]

[0040] Leakage plugging agent preparation process embodiment:

[0041] S1, put asphalt powder into a reactor, keep the stirring speed of the reactor at 100r / min, then heat the reactor to 120°C, add organic clay, sepiolite fiber (diameter of 15-30μm, length of 1-2mm), polyurethane (TPU) powder particles (particle size of 300-500μm) in sequence, and stir for 1 hour;

[0042] S2, add rock fiber, elastic graphite (particle size 5-40 μm), and nano-SiO2 (particle size 300-800 nm) to S1 in sequence and stir for 3 hours;

[0043] S3, extrude S2 into granules through a twin-screw extruder, and then crush and sieve to make a granular material with a particle size of 0.5 to 3 mm.

[0044] Comparative Example 1:

[0045] In Example 1, except that no polyurethane powder particles were added and the amount of elastic graphite added was increased to 22 wt %, the rest was the same as in Example 1.

[0046] Comparative Example 2:

[0047] In Example 1, except that the rock fiber is replaced by modified plant fiber, the rest is the same as in Example 1.

[0048] Comparative Example 3:

[0049] Except that the asphalt powder is replaced by modified paraffin wax, all components are physically mixed to obtain a powdery material, and the rest is the same as in the embodiment.

[0050] Performance indicators and comparative experiments

[0051] The base slurry of the oil-based drilling fluid is: 0# diesel + 3.0-5.0wt% emulsifier + 2.0wt% wetting agent + 1.5wt% emulsified viscosity enhancer + 25wt% brine + 3.0wt% organic soil + 2.0wt% CaO + 6wt% filtration reducer, with a density of 1.10g / cm3 and an oil-water ratio of 80:20.

[0052] 1) Compatibility performance test

[0053] Take 1000mL of base slurry, add 5% plugging agent sample, stir with a high-speed stirrer at 11000r / min for 5min, heat roll at 180℃ for 16 hours, cool to room temperature, stir at 4000r / min for 6min, and measure the performance of the base slurry and the comparative example after adding the sample. The test conditions of the base slurry and the sample after adding should be completely consistent.

[0054]

[0055] It can be seen from the experimental results in Table 1 that after the plugging agent of the present invention is added, the rheological properties and electrical stability of the oil-based drilling fluid do not change much, and the medium-pressure water loss and high-temperature and high-pressure water loss are significantly reduced. It can be seen that the plugging agents of Examples 1 to 5 of the present invention have good compatibility with the drilling fluid and have a good plugging effect. The compatibility and plugging effect of Comparative Examples 1 and 3 can also meet the requirements. The dynamic-plastic ratio of Comparative Example 2 becomes significantly larger, mainly because the modified plant fiber increases the viscosity of the oil-based drilling fluid and affects the rheological properties.

[0056] 2) Sealing strength test

[0057] A 10 wt% plugging agent sample was added to the base slurry, 4000 mL was taken and stirred at 300 r / min for 5 min, and a QD-1 plugging tester was used to simulate the leakage pressure test under the conditions of crack width of 0.5-9 mm and nitrogen pressure of 12 MPa, and the leakage volume, pressure strength and other parameters were recorded for 30 min.

[0058]

[0059] It can be seen from the test in Table 2 that after adding the plugging agent of the present invention, the oil-based drilling fluid can better plug the cracks of 0.5-9 mm and achieve the plugging effect. Comparative Example 1 has no high-strength elastic particles to support it, so the pressure bearing strength is reduced, resulting in a large filtration loss; Comparative Example 2 has poor plugging effect under high pressure due to insufficient strength of the bridging particles; Comparative Example 3 has poor plugging effect due to poor collective retention effect of the plugging materials.

Claims

1. An oil-based drilling fluid plugging agent, characterized in that: A granular material comprising the following components in percentage by mass: Asphalt powder: 15-28wt%; Organoclay: 6-16wt%; Rock fiber: 25-40wt%; Nano-SiO2: 5-12wt%; Sepiolite: 8-15wt%; Elastic graphite: 8-18wt%; Polyurethane (TPU) powder particles: 10-20wt%.

2. The oil-based drilling fluid plugging agent according to claim 1, characterized in that: The particle size of the granular material is 0.5 to 3 mm.

3. The oil-based drilling fluid plugging agent according to claim 1, characterized in that: The rock fiber has a diameter of 500-800 nm and a length of 100-200 μm.

4. The oil-based drilling fluid plugging agent according to claim 1, characterized in that: The particle size of the nano-SiO2 is 300-800nm.

5. The oil-based drilling fluid plugging agent according to claim 1, characterized in that: The sepiolite is sepiolite fiber with a diameter of 15 to 30 μm and a length of 1 to 2 mm.

6. The oil-based drilling fluid plugging agent according to claim 1, characterized in that: The elastic graphite particles have a particle size of 5 to 40 μm.

7. The oil-based drilling fluid plugging agent according to claim 1, characterized in that: The particle size of the polyurethane (TPU) powder particles is 300-500 μm.

8. The oil-based drilling fluid plugging agent according to any one of claims 1 to 7, characterized in that: The rock fiber is made of basalt and granite as raw materials, and is produced through crushing, high-temperature melting, alloy drawing and cutting.

9. The oil-based drilling fluid plugging agent according to claim 8, characterized in that: The preparation method of the rock fiber is as follows: basalt and granite are mixed and crushed into fine particles of 40 to 80 meshes in a mechanical crusher at a mass ratio of 7:3, and then put into a basalt furnace, melted and mixed evenly at a temperature of 1600°C, and then drawn at high speed through an alloy wire drawing plate to form fibers, and the surface of the drawn fibers is infiltrated with polyether modified silicone SF309, and then dried and processed by a cutting machine to obtain the fiber.

10. A method for preparing the oil-based drilling fluid plugging agent according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1, put asphalt powder into the reactor, keep the stirring speed of the reactor at 100r / min, then heat the reactor to 120°C, add organoclay, sepiolite and polyurethane (TPU) in sequence, and stir for 1 hour; S2, add rock fiber, elastic graphite and nano-SiO2 to S1 in sequence and stir for 3 hours; S2 is extruded into granules by a twin-screw extruder, and then crushed and sieved to form a granular material.

11. The method for preparing the oil-based drilling fluid plugging agent according to claim 10, characterized in that: The particle size of the granular material is 0.5 to 3 mm.

Citation Information

Patent Citations

  • Preparation of nano blocking agent and oil-based drilling fluid

    CN116948609A

  • High-temperature-resistant plugging agent for drilling fluid and preparation method thereof

    CN104774598A

  • Plugging agent for drilling fluid and preparation method thereof

    CN114479779A

  • Plugging agent for oil-based drilling fluid as well as preparation method and application of plugging agent

    CN114479790A

  • Anti-sloughing oil-based drilling fluid suitable for deep shale gas broken stratum and preparation method thereof

    CN117186852A